Method for regulating and controlling luminescence characteristics of polyvinyl alcohol

PVA luminescent microspheres are prepared through droplet microfluidic control technology to regulate their aggregation structure and morphology, which solves the problem of regulating the luminescent characteristics of PVA clusters in the prior art, and improves the flexibility of luminescent intensity and emission wavelength, providing a new strategy for the design of PVA-based luminescent materials.

CN119875623APending Publication Date: 2025-04-25NORTH SICHUAN MEDICAL COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510080491.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to effectively regulate the cluster luminescence characteristics of polyvinyl alcohol (PVA), and most cluster luminescence systems have problems such as short emission wavelength, low luminescence quantum efficiency, and unclear conformational relationships.

Method used

Microdroplets in oil-in-water form are prepared by droplet microfluidic control technology, and evaporation of organic solvents causes PVA to gather at the oil-water interface to form luminescent clusters, thereby preparing luminescent microspheres. By adjusting the microsphere preparation conditions, such as the selection of organic solvents in the internal oil phase, components and concentration, components and concentration in the aqueous polyvinyl alcohol solution, the aggregation structure and morphology of PVA are regulated, thereby changing its luminous characteristics.

Benefits of technology

Effective regulation of PVA luminescence characteristics is achieved, flexibility of luminescence intensity and emission wavelength is enhanced, and the PVA cluster luminescence mechanism is further clarified, providing a new strategy for designing and regulating PVA-based luminescence materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875623A_ABST
    Figure CN119875623A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of non-traditional organic light-emitting materials, and discloses a method for regulating and controlling the light-emitting characteristic of polyvinyl alcohol, which comprises the following steps: by taking an organic solvent as an inner oil phase and a polyvinyl alcohol aqueous solution as an outer water phase, preparing oil-in-water micro-droplets by using a droplet micro-fluidic chip; standing the micro-droplets at a constant temperature to volatilize the organic solvent, curing to form monodisperse microspheres, and adjusting the preparation conditions of the microspheres to achieve the effect of regulating and controlling the luminescence characteristic of the polyvinyl alcohol; the microsphere preparation conditions comprise the type of an organic solvent, the components and the concentration of the organic solvent or a polyvinyl alcohol aqueous solution, the constant-temperature standing temperature of the micro-droplets, the initial particle size of the micro-droplets, and the concentration, the alcoholysis degree and the molecular weight of polyvinyl alcohol. According to the method, the aggregation structure and morphology of the PVA can be regulated and controlled from the microscale level to change the luminescence characteristic of the PVA, technical support is provided for cluster luminescence research of a cluster emission illuminant, and a new idea is provided for exploring the luminescence mechanism of a non-traditional organic luminescent material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of non-traditional organic luminescent materials, and in particular to a method for regulating the luminescent properties of polyvinyl alcohol. Background Art

[0002] Organic light-emitting materials refer to a class of materials made of organic compounds that can spontaneously emit light under the stimulation of an external electric field or light field. Traditional organic light-emitting materials, whether aggregation-induced emission (AIE) or aggregation fluorescence quenching (ACQ), generally use aromatic rings, aromatic heterocycles or simple repeating single-bond-multiple bond units as emission centers, have significant large conjugated structures, are easily excited and emit light in the form of single molecules, but also have problems such as poor stability and complex synthesis. In order to improve these problems, some unconventional light-emitting materials that lack significant conjugation have begun to enter people's field of vision. They usually have some traditional auxochromic groups (such as hydroxyl, carbonyl, carboxyl, cyano, thioether, sulfone, fatty amine, etc.). This special structure gives non-traditional organic light-emitting materials excellent water solubility, biocompatibility, easy preparation and environmental friendliness, and broadens the application range of organic light-emitting materials in the fields of bioimaging, drug delivery, sensors, etc.

[0003] Unconventional luminophores do not emit light in dilute solutions, but they often emit light in concentrated solutions or solid states, with typical AIE characteristics. This phenomenon was first discovered in polyamidoamine (PAMAM) dendrimers. In 2013, Tang Benzhong's research group reported the intrinsic luminescence of some natural products, such as starch, cellulose and bovine serum albumin, and proposed that the aggregation of electron-rich oxygen atoms leads to electron overlap and conformational rigidification, which is the cause of luminescence. This was verified by the photophysical properties of polyacrylonitrile (PAN). Clustered electron-rich units interact with each other in space, thereby reducing the energy gap and emitting in the visible light region. Due to the heterogeneity of cluster size and conformation, cluster luminophores usually have the characteristics of excitation wavelength dependence. The introduction of the theory of spatial interaction has promoted the discovery of more cluster luminescence systems and derived a series of new applications of cluster luminescence materials. However, since the current methods for studying the aggregation behavior of materials and their cluster luminescence characteristics are very single, it is not possible to directly determine whether a certain material has cluster luminescence characteristics; in addition, most reported cluster luminescence systems still have problems such as short emission wavelength, low luminescence quantum efficiency, and unclear conformational relationship. All these have hindered the discovery, research and application of cluster luminescent materials. Therefore, exploring and constructing new controllable aggregation pathways for materials, and then regulating the cluster luminescence properties of materials by regulating the clustering effect, will help further reveal the luminescence mechanism of cluster luminescence and promote the wider application of cluster luminescent materials.

[0004] Polyvinyl alcohol (PVA) is an environmentally friendly hydrophilic vinyl polymer generated by the hydrolysis of polyvinyl acetate (PVAc). The corresponding degree of hydrolysis determines the -OH content, which in turn affects the physical properties of the resulting PVA. PVA is one of the most produced synthetics in the world. Due to its low protein absorption rate and chemical resistance, it has a wide range of applications in medicine. Jingfei Wang et al. reported the unique intrinsic emission of PVA. Non-conjugated macromolecular polyvinyl alcohol (PVA) has almost no emission at low concentrations, but has enhanced emission in high-concentration solutions, solid powders, and formed films, showing obvious AIE characteristics. Jingfei Wang et al. explained the intrinsic emission of PVA using the cluster emission mechanism (CTE), but its aggregation structure and its regulation mechanism are still unclear. It is still a huge challenge for technicians in this field to change the luminescence properties of PVA by regulating the aggregation structure of PVA at the microscale level. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a method for regulating the luminescence properties of polyvinyl alcohol, aiming to change the cluster luminescence properties of PVA by regulating the aggregation structure and morphology of PVA at the microscale level, and to provide technical support for studying how to controllably construct a stable aggregation structure of materials to produce a clustering effect to regulate the cluster luminescence properties of materials.

[0006] To achieve the above-mentioned purpose, the present invention provides a method for regulating the luminescence characteristics of polyvinyl alcohol, which uses an organic solvent as an inner oil phase and a polyvinyl alcohol aqueous solution as an outer water phase, uses a droplet microfluidic chip to prepare water-in-oil microdroplets, and the microdroplets are allowed to stand at a constant temperature to volatilize the organic solvent and solidify to form monodisperse microspheres, and the effect of regulating the luminescence characteristics of polyvinyl alcohol is achieved by adjusting the microsphere preparation conditions; the microsphere preparation conditions include the selection of the organic solvent in the inner oil phase, the components and concentrations added to the organic solvent, the components and concentrations added to the polyvinyl alcohol aqueous solution, the constant temperature at which the microdroplets are allowed to stand, the initial particle size of the microdroplets, and the concentration, alcoholysis degree, and molecular weight of the polyvinyl alcohol in the polyvinyl alcohol aqueous solution.

[0007] The above method simply prepares organic solvent / polyvinyl alcohol microdroplets, and during the volatilization of the organic solvent, PVA aggregates at the oil-water interface to form luminescent clusters to obtain luminescent microspheres. The PVA aggregation structure and morphology are changed by regulating the selection of organic solvent in the internal oil phase, the components and concentrations added to the organic solvent, the components and concentrations added to the polyvinyl alcohol aqueous solution, the constant temperature of the microdroplets, the initial particle size of the microdroplets, and the concentration, alcoholysis degree, and molecular weight of the polyvinyl alcohol in the polyvinyl alcohol aqueous solution, thereby changing the fluorescent luminescence properties of the microspheres. The excitation wavelength dependence of the luminescent microspheres prepared by the present invention is likely due to the fact that the PVA side chain groups (-OH, -OCOCH3) form heterogeneous luminescent clusters. In order to verify this conjecture, the present invention conducted further experiments, and introduced substances containing rich ester groups (such as polyvinyl acetate PVAc, polymethyl methacrylate PMMA, polycaprolactone PCL) into the inner oil phase organic solvent chloroform. By regulating the type and concentration of the solute added to the inner oil phase organic solvent, the type of organic solvent in the inner oil phase, the components and concentration added to the polyvinyl alcohol aqueous solution, the constant temperature of the microdroplets, the initial particle size of the microdroplets, and the concentration, degree of alcoholysis, and molecular weight of polyvinyl alcohol in the polyvinyl alcohol aqueous solution, the aggregation structure and morphology are regulated from a microscale, which is specifically manifested as a change in fluorescence intensity. The control method of the present invention is also applicable to other non-traditional organic light-emitting materials, and can provide new ideas for exploring the luminescence mechanism of non-traditional organic light-emitting materials.

[0008] Further, the organic solvent includes chloroform and dichloromethane. It is understood that the organic solvent can also be selected from organic solvents having similar physical and chemical properties to chloroform, dichloromethane or a mixed homogeneous solvent thereof.

[0009] Furthermore, the components added to the organic solvent include polyvinyl acetate, polymethyl methacrylate and polycaprolactone, the molecular weight of the polyvinyl acetate includes 50,000 and 300,000, the molecular weight of the polymethyl methacrylate includes 15,000 and 350,000, and the molecular weight of the polycaprolactone includes 50,000-60,000 and 80,000-100,000.

[0010] Furthermore, the concentration of the component added to the organic solvent in the organic solvent includes 0.2 g / 100 mL, 1 g / 100 mL, 5 g / 100 mL, 10 g / 100 mL and 15 g / 100 mL.

[0011] Furthermore, the components added to the polyvinyl alcohol aqueous solution include glycerol, polyethylene glycol and a surfactant, the molecular weight of the polyethylene glycol is 400, and the surfactant includes an anionic surfactant and a nonionic pre-copolymer surfactant.

[0012] Furthermore, the volume concentration of the glycerol includes 10.0% and 30.0%, the volume concentration of the polyethylene glycol is 10.0%, and the concentration of the surfactant is 0.1 g / 100 mL.

[0013] Furthermore, the micro-droplet constant temperature includes 5°C, 20°C, and 30°C.

[0014] Furthermore, the initial particle sizes of the microdroplets include 105 μm, 145 μm, and 175 μm.

[0015] Furthermore, the concentration of polyvinyl alcohol in the polyvinyl alcohol aqueous solution includes 0.2 g / 100 mL, 0.5 g / 100 mL, 1 g / 100 mL, 2 g / 100 mL, 3 g / 100 mL, and 5 g / 100 mL.

[0016] Furthermore, the alcoholysis degree of the polyvinyl alcohol in the polyvinyl alcohol aqueous solution includes 98%, 87-89% and 87-90%, and the molecular weight includes 13000-23000, 30000-70000 and 146000-186000.

[0017] Compared with the prior art, the present invention provides a new method for regulating the luminescent properties of polyvinyl alcohol, a non-traditional organic luminescent material. The method is based on droplet microfluidics technology, combined with a solvent volatilization method to prepare monodisperse microspheres, and the effect of regulating the luminescent properties of polyvinyl alcohol is achieved by adjusting the preparation conditions of the microspheres. The method of the present invention not only further explains the luminescent mechanism of PVA clusters, but also provides a new and reliable strategy for designing and regulating PVA-based luminescent materials. The present invention adopts droplet microfluidics technology to prepare microdroplets, which not only provides a controllable interface environment for PVA, but also facilitates real-time observation and regulation. At the same time, only a small amount of reagent is required to prepare microdroplets, which effectively reduces the waste of reagents. Thanks to the precise control ability of droplet microfluidics technology, the method of the present invention can freely design the composition of the oil-water two-phase interface, regulate the aggregation structure and morphology on a microscale, thereby changing its luminescent properties such as luminescent intensity and emission wavelength. In addition, the method of the present invention is also applicable to other non-traditional organic luminescent materials, providing inspiration and technical support for discovering whether the material has aggregated luminescent properties and studying the aggregated luminescent properties of luminescent materials, and can provide new ideas for exploring the luminescent mechanism of non-traditional organic luminescent materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the preparation of chloroform / PVA microdroplets in Example 1;

[0019] Figure 2 This is a schematic diagram of the change process of the micro-droplets as the organic solvent evaporates in Example 1;

[0020] Figure 3Schematic diagram of the micro-droplets in Example 1 evaporating into micro-spheres and then being excited by laser;

[0021] Figure 4 The fluorescence image and bright field image of the microdroplets volatilizing with the organic solvent in Example 1;

[0022] Figure 5 is the particle size change curve of the micro droplets as the organic solvent evaporates in Example 1;

[0023] Figure 6 is the fluorescence intensity variation curve of the microdroplets as the organic solvent evaporates in Example 1;

[0024] Figure 7 is a microscopic image of the microdroplets and microspheres prepared in Example 2;

[0025] Figure 8 is the size distribution diagram of the microdroplets and microspheres prepared in Example 2;

[0026] Fig. 9 The fluorescent image and bright field image of the microspheres prepared in Example 2;

[0027] Fig.10 The fluorescence intensity comparison of the microspheres prepared in Example 2;

[0028] Fig.11 The fluorescent image and bright field image of the microspheres prepared in Example 3;

[0029] Fig.12 This is a comparison chart of the fluorescence intensity of the microspheres prepared in Example 4;

[0030] Fig.13 This is a comparison chart of the fluorescence intensity of the microspheres prepared in Example 5;

[0031] Fig.14 This is a comparison chart of the fluorescence intensity of the microspheres prepared in Example 6;

[0032] Fig.15 The fluorescent image and bright field image of the microdroplets prepared in Example 7 as the organic solvent evaporates;

[0033] Fig.16 is the droplet size change curve of the micro-droplets prepared in Example 7 as the organic solvent evaporates;

[0034] Fig.17 is the fluorescence intensity variation curve of the microdroplets prepared in Example 7 as the organic solvent evaporates;

[0035] Fig.18 is a microscopic image of the initial microdroplets and composite microspheres prepared in Example 8;

[0036] Fig.19 is a scanning electron microscope image of the composite microspheres prepared in Example 8;

[0037] Fig. 20 The fluorescent image and bright field image of the composite microspheres prepared in Example 8;

[0038] Fig.21 The fluorescence intensity comparison of the composite microspheres prepared in Example 8;

[0039] Fig. 22 is a comparison of the fluorescence intensity of the composite microspheres prepared in Example 9;

[0040] Fig.23 is a comparison of the fluorescence intensity of the composite microspheres prepared in Example 10;

[0041] Fig.24 The fluorescence intensity comparison of the composite microspheres prepared in Example 11;

[0042] Fig.25 is a comparison chart of the fluorescence intensity of the composite microspheres prepared in Example 12;

[0043] Fig.26 is a fluorescence intensity comparison diagram of the composite microspheres prepared in Example 13;

[0044] Fig. 27 This is a comparison chart of the fluorescence intensity of the composite microspheres prepared in Example 14.

[0045] Fig.28 This is a comparison chart of the fluorescence intensity of the composite microspheres prepared in Example 15. DETAILED DESCRIPTION

[0046] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below in conjunction with specific embodiments.

[0047] Embodiments 1 to 6 provide a method for preparing PVA microspheres, which comprises the following steps:

[0048] S1. preparing an inner oil phase (dispersed phase) and an outer water phase (continuous phase), wherein the inner oil phase comprises chloroform and dichloromethane, and the outer water phase comprises a polyvinyl alcohol solution and a polyvinyl alcohol solution doped with other materials, wherein the other materials comprise glycerol, polyethylene glycol and a surfactant;

[0049] S2, injecting the inner oil phase into the organic phase microchannel of the droplet microfluidic chip through an external injection pump, and injecting the outer water phase into the water phase microchannel of the droplet microfluidic chip, and obtaining microdroplets of oil-in-water morphology of different particle sizes by adjusting the flow rates of the inner oil phase and the outer water phase, and collecting the samples with a collection container containing the corresponding outer water phase solution;

[0050] S3. The collected microdroplets are placed in a 5°C constant temperature box and allowed to stand at a constant temperature until the organic solvent in the inner oil phase evaporates completely to obtain PVA microspheres.

[0051] The characterization method of the PVA microspheres prepared in Examples 1 to 6 is as follows:

[0052] 1. Use ImageJ software to measure the particle size of microdroplets and PVA microspheres;

[0053] 2. Use a laser confocal microscope to observe the changes in the fluorescence intensity of the microdroplets during the evaporation of the organic solvent. Perform Z-axis layer scanning of the PVA microspheres and use Imaris Viewer software for post-processing to display the luminescent structure of the PVA microspheres.

[0054] Embodiments 7 to 15 provide a method for preparing PVA composite microspheres (PVAc-PVA, PMMA-PVA, PCL-PVA), which comprises the following steps:

[0055] S1. preparing an inner oil phase (dispersed phase) and an outer water phase (continuous phase), wherein the inner oil phase is a chloroform solution containing a solute, wherein the solute includes polyvinyl acetate (PVAc), polymethyl methacrylate (PMMA) and polycaprolactone (PCL), and the outer water phase includes a polyvinyl alcohol solution and a polyvinyl alcohol solution doped with other materials, wherein the other materials include glycerol, polyethylene glycol and a surfactant;

[0056] S2, injecting the inner oil phase into the organic phase microchannel of the droplet microfluidic chip through an external injection pump, and injecting the outer water phase into the water phase microchannel of the droplet microfluidic chip, and obtaining microdroplets of oil-in-water morphology of different particle sizes by adjusting the flow rates of the inner oil phase and the outer water phase, and collecting the samples with a collection container containing the corresponding outer water phase solution;

[0057] S3, placing the collected microdroplets in a thermostat at different temperatures and keeping them still at a constant temperature, and obtaining PVA composite microspheres after the organic solvent in the inner oil phase evaporates completely;

[0058] S4. The PVA composite microspheres dispersed in the external aqueous phase solution are precipitated at the bottom of the centrifuge tube by centrifugation - the supernatant is removed - water is added - centrifugation is repeated three times, and finally the PVA composite microspheres are dispersed in water, and then the PVA composite microspheres are freeze-dried.

[0059] The characterization method of the PVA composite microspheres prepared in Examples 7 to 15 is as follows:

[0060] 1. Use imagej software to measure the particle size of microdroplets and PVA composite microspheres;

[0061] 2. Use laser confocal microscopy to observe the changes in the fluorescence intensity of the microdroplets during the evaporation of the organic solvent. The composite microspheres show photoluminescence characteristics. The PVA composite microspheres are scanned on the Z axis and post-processed with Imaris Viewer software to display the luminescent structure of the PVA composite microspheres.

[0062] 3. Observe the morphology of PVA composite microspheres by scanning electron microscopy.

[0063] Embodiment 1:

[0064] This example investigates the fluorescence changes of the prepared chloroform / PVA microdroplets during the evaporation of the organic solvent, and the detailed process is as follows:

[0065] The inner oil phase is chloroform solvent, and the outer water phase is 0.5% (w / v) PVA2 solution. The average molecular weight of PVA2 is 13000-23000, and the degree of alcoholysis is 87-89%. The two phases are pumped into the microfluidic device by a precision injection pump to form chloroform / PVA microdroplets in the form of oil-in-water. The process of microdroplet formation is shown in Figure 1 As shown in the figure, the microdroplets form microspheres as the organic solvent evaporates. The change process is shown in Figure 2 As shown. A laser confocal microscope (Olympus SpinSR10) was used to observe the change from microdroplets to microspheres (room temperature 22°C). The microscope parameters were fixed, laser 1 (405nm: 50mW) laser intensity was 100%, integration time was 500ms; laser 2 (488nm: 100mW) laser intensity was 100%, integration time was 500ms; laser 3 (561nm: 100mW) laser intensity was 100%, integration time was 500ms. See Figures 4 to 6 , as the organic solvent evaporates, the particle size of the microdroplets gradually decreases and the fluorescence gradually appears; Figure 3 As shown, under the excitation of lasers of different wavelengths, the microspheres exhibit fluorescence of different colors, indicating that PVA has excitation wavelength dependence. This is because PVA aggregates at the oil-water interface as the organic solvent in the microdroplets evaporates to form luminescent clusters.

[0066] Embodiment 2:

[0067] This example investigates the effect of the PVA concentration in the external aqueous phase on the fluorescence intensity of the microspheres, and the specific operation is as follows:

[0068] The inner oil phase is chloroform, and the outer water phase is PVA2 solution. The average molecular weight of PVA2 is 13000-23000, the degree of alcoholysis is 87-89%, and the concentrations of PVA2 solutions are 0.2% (w / v), 0.5% (w / v), 1.0% (w / v), 2.0% (w / v), 4.0% (w / v), and 5.0% (w / v), respectively. Chloroform is sheared into microdroplets with a particle size of about 145 μm by the above-mentioned external water phase solution in the microchannel. The microdroplets have extremely high monodispersity, and the coefficients of variation (CV values) are 3.1%, 1.8%, 2.2%, 2.5%, 2.5%, and 2.3%, respectively. After being placed in a 5°C constant temperature box for about 5 hours, the organic solvent in the microdroplets evaporates completely to obtain microspheres, and the CV values ​​of the microspheres are 4.9%, 4.8%, 4.3%, 4.1%, 4.9%, and 4.8%, respectively. Figure 7 is a microscope photo of the initial microdroplets and microspheres. The size distribution of the initial microdroplets and the corresponding formed microspheres is shown in Figure 8 The microspheres were observed under a laser confocal microscope, with the same parameters as in Example 1. Fig. 9 The fluorescence image and bright field image of the microspheres are shown in Figure 2. The fluorescence intensity of the microspheres under three excitation lights is counted. The results are shown in Figure 2. Fig.10 When the PVA concentration is 0.5% (w / v), the blue and green emissions are strongest under 405nm and 488nm laser excitation; when the PVA concentration is in the range of 0.5% (w / v)-5.0% (w / v), the blue and green emissions gradually weaken with the increase of PVA concentration; in addition, under 561nm laser excitation, the emission of the microspheres in the red region reaches the strongest at 2.0% (w / v) PVA concentration.

[0069] Embodiment 3:

[0070] This example investigates the effect of the internal oil phase organic solvent on the fluorescence intensity of the microspheres, and the specific operation is as follows:

[0071] The inner oil phase is chloroform (CHCl3) and dichloromethane (CH2Cl2), and the outer water phase is 2.0% (w / v) PVA2 solution. The average molecular weight of PVA2 is 13000-23000, and the alcoholysis degree is 87-89%. Chloroform and dichloromethane are sheared into micro droplets with a particle size of about 145 μm by the outer water phase solution in the microchannel. After being placed in a 5°C constant temperature box for about 5 hours, the organic solvent in the micro droplets is completely evaporated to obtain microspheres, which are observed under confocal microscope. The parameters are the same as those in Example 1. The fluorescence image comparison results are shown in FIG. Fig.11 As shown, the process of PVA aggregation at the interface to form luminescent clusters is affected by the internal phase solvent. Under 405nm, 488nm and 561nm laser excitation, the microspheres prepared with chloroform as the internal phase solvent have stronger emission in the blue region; on the contrary, the microspheres prepared with dichloromethane as the internal phase solvent have stronger emission in the green and red regions.

[0072] Embodiment 4:

[0073] This example investigates the effect of the alcoholysis degree and molecular weight of PVA in the external water phase on the fluorescence intensity of the microspheres. The specific operation is as follows:

[0074] The inner oil phase is chloroform, and the outer aqueous phase PVA solution includes PVA1 (molecular weight of 13000-23000, alcoholysis degree of 98%), PVA2 (molecular weight of 13000-23000, alcoholysis degree of 87-89%), PVA3 (molecular weight of 30000-70000, alcoholysis degree of 87-90%), and PVA4 (molecular weight of 146000-186000, alcoholysis degree of 87-89%), and the concentration is 0.5% (w / v). Chloroform is sheared into micro droplets with a particle size of about 145 μm by the above-mentioned outer aqueous phase solution in the microchannel, and the microspheres are obtained after the chloroform in the micro droplets is completely evaporated in a 5°C constant temperature box for about 5 hours, and then placed under confocal observation, and the parameters are the same as those in Example 1. The results of the change in fluorescence intensity are shown in FIG. Fig.12 As shown in the figure, the microspheres prepared by using PVA with the same molecular weight under 405nm, 488nm and 561nm laser excitation, the microspheres with high PVA alcoholysis degree emit more strongly in the blue and red regions, and emit weaker in the green region; the microspheres prepared by using PVA with the same alcoholysis degree under 405nm, 488nm and 561nm laser excitation, as the molecular weight of PVA increases, the microspheres emit gradually more in the blue and red regions under 405nm and 561nm laser excitation. On the contrary, under 488nm laser excitation, the emission in the green region gradually weakens as the molecular weight of PVA increases.

[0075] Embodiment 5:

[0076] This example investigates the effect of changes in components in the external water phase on the fluorescence intensity of the microspheres. The specific operation is as follows:

[0077] The inner oil phase is chloroform, which is doped in the outer aqueous phase solution. Other materials such as glycerol (Glycerol) or polyethylene glycol (PEG, molecular weight 400) are added to the 0.5% (w / v) PVA2 aqueous solution. The prepared outer aqueous phase solutions are 0.5% (w / v) PVA2 + 10.0% (v / v) Glycerol, 0.5% (w / v) PVA2 + 30.0% (v / v) Glycerol, and 0.5% (w / v) PVA2 + 10.0% (v / v) PEG400. Chloroform is sheared into microdroplets with a particle size of about 145 μm by the above-mentioned outer aqueous phase solutions in the microchannel. The organic solvent in the microdroplets is completely evaporated after being placed in a 5°C constant temperature box for about 5 hours to obtain microspheres, which are observed under confocal microscope. The parameters are the same as those in Example 1. The fluorescence intensity change results are shown in FIG. Fig.13As shown, the additional introduction of solvents and solutes in the external aqueous phase will affect the interaction and intermolecular distance between PVA molecules, thereby playing a role in regulating the cluster luminescence characteristics of the microspheres. Under 405nm, 488nm, and 561nm laser excitation, the microspheres obtained in this example, compared with 0.5% (w / v) PVA2 aqueous solution, the microspheres prepared by additionally introducing solvents and solutes in the external aqueous phase showed a weakened emission in the blue, green, and red regions.

[0078] Embodiment 6:

[0079] This example investigates the effect of the interaction of surfactants at the interface on the fluorescence intensity of microspheres. The specific operation is as follows:

[0080] The inner oil phase is chloroform, and the outer water phase contains 0.5% (w / v) PVA2 aqueous solution, and other surfactants are introduced to compete with it. The prepared outer water phase solutions are 0.5% (w / v) PVA2 + 0.1% (w / v) F68 and 0.5% (w / v) PVA2 + 0.1% (w / v) SDS. Chloroform is sheared into micro droplets with a particle size of about 145 μm by the above-mentioned outer water phase solution in the microchannel. The organic solvent in the micro droplets is completely evaporated after being placed in a 5°C constant temperature box for about 5 hours to obtain microspheres, which are then observed under confocal microscope with the same parameters as in Example 1. The fluorescence intensity change results are shown in Figure 2. Fig.14 As shown, the additionally introduced other surfactants will compete with the PVA molecules at the oil-water interface, thereby affecting the distribution and aggregation of the PVA molecules at the oil-water interface, thereby playing a role in regulating the luminescence characteristics of the microsphere cluster. Under 405nm, 488nm, and 561nm laser excitation, the microspheres prepared by adding surfactants have significantly weakened emission in the blue, green, and red regions.

[0081] Embodiment 7:

[0082] This example investigates the effect of the introduction of molecular functional groups such as ester groups on the fluorescence intensity. The specific operation is the same as that of Example 1. The only difference from Example 1 is that the inner oil phase is a chloroform solution containing 0.2% (w / v) PVAc (the average molecular weight of PVAc is 50,000), and PVAc contains a large number of ester groups; the outer water phase is a 5.0% (w / v) PVA2 solution. Figures 15 to 17 It can be seen that, as the organic solvent evaporates, the particle size of the microdroplets prepared in this embodiment gradually decreases, the fluorescence gradually appears, and the fluorescence intensity gradually increases.

[0083] Embodiment 8:

[0084] This example investigates the effect of PVAc concentration in the internal oil phase on the fluorescence intensity of PVAc-PVA composite microspheres, and the specific operation is as follows:

[0085] The inner oil phase is chloroform containing solute PVAc (the average molecular weight of PVAc is 50000), and the PVAc concentrations are 0.2% (w / v), 1.0% (w / v), 5.0% (w / v), 10.0% (w / v), and 15.0% (w / v); the outer water phase is 5.0% (w / v) PVA2 solution. The inner oil phase is sheared by the outer water phase in the microchannel to form microdroplets with a particle size of about 145μm, and the CV values ​​of the microdroplets are 1.8%, 1.9%, 1.6%, 2.1%, and 1.5%, respectively. The organic solvent in the microdroplets is completely evaporated in a 5℃ constant temperature box for about 48 hours to obtain PVAc-PVA composite microspheres, and the CV values ​​of the composite microspheres are 3.4%, 3.9%, 2.2%, 1.3%, and 1.1%, respectively. Fig.18 Figure 2 is a microscopic image of the initial microdroplets and the composite microspheres. It can be seen that when the initial microdroplet size is the same, the composite microsphere size increases with the increase of PVAc concentration. The scanning electron microscopy results of the composite microspheres prepared in this embodiment are shown in Figure 2. Fig.19 The composite microspheres were observed under confocal microscope with the same parameters as in Example 1. Fig. 20 The fluorescence image and bright field image of the composite microspheres prepared in this example are shown in Figure 2. The fluorescence intensity of the composite microspheres under three excitation lights is counted. Fig.21 Under 405nm, 488nm, and 561nm laser excitation, when the PVAc concentration was in the range of 0.2% (w / v)-15.0% (w / v), as the PVAc concentration increased, the conformational changes may be caused by the increase in the ester content in the aggregate clusters, causing the composite microspheres to show a weakened emission in the blue, green, and red regions. Therefore, regulating the solute concentration in the inner oil phase will also affect the volatilization process of the inner oil phase solvent and the assembly behavior and aggregation process of the inner oil phase solute, thereby causing changes in the luminescence characteristics of the composite microspheres.

[0086] It should be noted that, in this embodiment, the internal oil phase is an organic solution phase containing the solute PVAc, and its concentration can be selectively regulated when preparing the solution. In addition, the process of transforming the microdroplets into composite microspheres is essentially a process in which the solute concentration in the internal oil phase gradually increases. Therefore, the present invention is also applicable to studying the luminescent properties of luminescent materials dissolved in organic solvents and the molecular assembly behavior that may exist in their aggregation process.

[0087] Embodiment 9:

[0088] This example investigates the effect of ambient temperature on the fluorescence intensity of PVAc-PVA composite microspheres, and the specific operation is as follows:

[0089] The inner oil phase is a chloroform solution containing 0.2% (w / v) PVAc (the average molecular weight of PVAc is 50,000), and the outer water phase is a 5.0% (w / v) PVA2 solution. The inner oil phase is sheared by the outer water phase in the microchannel to form microdroplets with a particle size of about 145 μm. Three portions are placed in a constant temperature box at 5°C, 20°C, and 30°C for about 48 hours. After the organic solvent in the microdroplets evaporates completely, PVAc-PVA composite microspheres are obtained and observed under confocal microscope. The parameters are the same as those in Example 1. The fluorescence intensity comparison results of the composite microspheres are shown in Fig. 22 , temperature will affect the aggregation of PVAc and PVA. In a low temperature environment, the restricted molecular motion will increase the fluorescence intensity of the microspheres. The composite microspheres obtained in this example emit the strongest light in the blue, green and red regions under 405nm, 488nm and 561nm laser excitation at 5°C. The fluorescence of the composite microspheres will be significantly weakened when the temperature is raised to 20 or 30°C.

[0090] Embodiment 10:

[0091] This example investigates the effect of the initial droplet size on the fluorescence intensity of the PVAc-PVA composite microspheres, and the specific operation is as follows:

[0092] The inner oil phase is a chloroform solution containing 0.2% (w / v) PVAc (the average molecular weight of PVAc is 50,000), and the outer water phase is a 5.0% (w / v) PVA2 solution. The inner oil phase is sheared by the outer water phase in the microchannel into microdroplets with particle sizes of approximately 105 μm, 145 μm, and 175 μm, respectively, and placed in a 5°C constant temperature box for about 48 hours to obtain PVAc-PVA composite microspheres after the organic solvent in the microdroplets evaporates completely. After complete evaporation, the PVAc-PVA composite microspheres are observed under confocal microscope with the same parameters as in Example 1. The fluorescence intensity comparison results of the composite microspheres are shown in Figure 1. Fig.23 The initial droplet size will affect the volatilization rate of the droplets and the assembly morphology of PVA at the interface, and thus can regulate the cluster luminescence characteristics of the composite microspheres. Under 405nm, 488nm, and 561nm laser excitation, the composite microspheres obtained in this example with a particle size of 145μm prepared from three different initial droplet particle sizes have the weakest emission in the blue region, and the strongest emission in the green and red regions.

[0093] Embodiment 11:

[0094] This example investigates the effect of the PVA concentration in the external aqueous phase on the fluorescence intensity of the PVAc-PVA composite microspheres, and the specific operation is as follows:

[0095] The inner oil phase is a chloroform solution containing 0.2% (w / v) PVAc (the average molecular weight of PVAc is 50,000), and the outer aqueous phase is a PVA2 solution. The PVA2 concentrations are 0.2% (w / v), 0.5% (w / v), 1.0% (w / v), 2.0% (w / v), 4.0% (w / v), and 5.0% (w / v), respectively. The inner oil phase is sheared by the outer aqueous phase in the microchannel to form microdroplets with a particle size of about 145 μm. The microdroplets are placed in a 5°C constant temperature box for about 48 hours until the organic solvent in the microdroplets evaporates completely to obtain PVAc-PVA composite microspheres, which are observed under confocal microscope with the same parameters as in Example 1. The fluorescence intensity change results of the composite microspheres are shown in Figure 1. Fig.24 When the PVA concentration is in the range of 0.2% (w / v)-2.0% (w / v), under 405nm and 488nm laser excitation, the blue and green emissions gradually weaken as the PVA concentration increases; when the PVA concentration is in the range of 2.0% (w / v)-5.0% (w / v), under 405nm and 488nm laser excitation, the blue and green emissions gradually increase as the PVA concentration increases; when the PVA concentration is in the range of 0.2% (w / v)-1.0% (w / v), under 561nm laser excitation, the red emission gradually weakens as the PVA concentration increases; when the PVA concentration is in the range of 1.0% (w / v)-5.0% (w / v), under 561nm laser excitation, the red emission gradually increases as the PVA concentration increases.

[0096] Embodiment 12:

[0097] This example investigates the effect of the alcoholysis degree and molecular weight of PVA in the external water phase on the fluorescence intensity of PVAc-PVA composite microspheres. The specific operation is as follows:

[0098] The inner oil phase is a chloroform solution containing 0.2% (w / v) PVAc (the average molecular weight of PVAc is 50000), and the outer aqueous phase PVA solution includes PVA1 (molecular weight is 13000-23000, alcoholysis degree is 98%), PVA2 (molecular weight is 13000-23000, alcoholysis degree is 87-89%), PVA3 (molecular weight is 30000-70000, alcoholysis degree is 87-90%), and PVA4 (molecular weight is 146000-186000, alcoholysis degree is 87-89%), and the concentration is 0.5% (w / v). The inner oil phase is sheared into droplets with a particle size of about 145 μm by the above-mentioned outer aqueous phase solution in the microchannel, placed in a 5° C. thermostat for about 48 hours until the organic solvent in the micro droplets is completely volatilized to obtain PVAc-PVA composite microspheres, and placed under confocal observation, and the parameters are the same as those in Example 1. The fluorescence intensity change results are as follows Fig.25As shown, under 405nm, 488nm and 561nm laser excitation, the composite microspheres with high alcoholysis degree of PVA prepared by the same molecular weight have weaker emission in the blue, green and red regions; under 405nm, 488nm and 561nm laser excitation, compared with the composite microspheres prepared by PVA with a molecular weight of 13000-23000, the composite microspheres prepared when the PVA molecular weight increases to 30000-70000 have enhanced blue emission under 405nm laser excitation; when the PVA molecular weight increases to 146000-186000, the blue emission of the composite microspheres under 405nm laser excitation weakens; in addition, under 488nm and 561nm laser excitation, the green and red emission of the composite microspheres increases with the increase of PVA molecular weight.

[0099] Embodiment 13:

[0100] This example investigates the effect of changes in components in the external water phase on the fluorescence intensity of PVAc-PVA composite microspheres, and the specific operation is as follows:

[0101] The inner oil phase is a chloroform solution containing 0.2% (w / v) PVAc (the average molecular weight of PVAc is 50000), which is doped in the outer aqueous phase solution. Glycerol (Glycerol) or polyethylene glycol (PEG, molecular weight is 400) is added to the 0.5% (w / v) PVA2 aqueous solution. The prepared outer aqueous phase solutions are 0.5% (w / v) PVA2+10.0% (v / v) Glycerol, 0.5% (w / v) PVA2+30.0% (v / v) Glycerol, and 0.5% (w / v) PVA2+10.0% (v / v) PEG400. The inner oil phase is sheared by the outer aqueous phase in the microchannel to form microdroplets with a particle size of about 145 μm, which are placed in a 5° C. incubator for about 48 hours until the organic solvent in the microdroplets is completely volatilized to obtain PVAc-PVA composite microspheres, which are observed under confocal microscope, and the parameters are the same as those in Example 1. The fluorescence intensity change results are as follows Fig.26As shown, the additional introduction of solvents and solutes will affect the interaction between PVA molecules and the molecular distance, and thus can regulate the cluster luminescence properties of the composite microspheres. Compared with PVA microspheres, PVAc-PVA composite microspheres contain more ester groups, so the introduction of solvents and solutes will have different effects on the change of the luminescence properties of the final formed microspheres. Under 405nm, 488nm, and 561nm laser excitation, the composite microspheres obtained in this embodiment, prepared by adding an additional glycerol external phase, showed enhanced emission in the blue, green, and red regions; with the increase of glycerol added, the blue emission attenuated, while the green and red emissions were significantly enhanced; the composite microspheres prepared by adding an additional polyethylene glycol external phase had enhanced emission in the blue and green regions and weakened emission in the red region.

[0102] Embodiment 14:

[0103] This example investigates the effect of the interaction of surfactants at the interface on the fluorescence intensity of PVAc-PVA composite microspheres, and the specific operation is as follows:

[0104] The inner oil phase is a chloroform solution containing 0.2% (w / v) PVAc (the average molecular weight of PVAc is 50,000), and the outer aqueous phase contains, in addition to a 0.5% (w / v) PVA2 aqueous solution, other surfactants are additionally introduced to compete with it. The prepared outer aqueous phase solutions are 0.5% (w / v) PVA2 + 0.1% (w / v) F68 and 0.5% (w / v) PVA2 + 0.1% (w / v) SDS. The inner oil phase is sheared by the outer aqueous phase in the microchannel to form microdroplets with a particle size of about 145 μm, which are placed in a 5°C constant temperature box for about 48 hours to completely evaporate the organic solvent in the microdroplets to obtain PVAc-PVA composite microspheres, which are observed under confocal microscope with the same parameters as in Example 1. The results of the fluorescence intensity change are shown in the figure. Fig. 27 As shown, the additionally introduced other surfactants will compete with the PVA molecules at the oil-water interface, affecting the distribution and aggregation of the PVA molecules at the oil-water interface, as well as the combination of the PVA molecules and the PVAc molecules, thereby regulating the cluster luminescence characteristics of the composite microspheres. Under 405nm laser excitation, the composite microspheres obtained in this example, the composite microspheres prepared by introducing F68 have enhanced blue emission, while the composite microspheres prepared by introducing SDS have weakened blue emission; under 488nm and 561nm laser excitation, the composite microspheres obtained in this example, the composite microspheres prepared by introducing F68 or SDS have significantly weakened green and red emissions.

[0105] Embodiment 15:

[0106] This example investigates the effect of the type and molecular weight of the internal phase solute on the fluorescence intensity of the composite microspheres. The specific operation is as follows:

[0107] The inner oil phases are chloroform solutions containing 1.0% (w / v) PVAc1 (the average molecular weight of PVAc1 is 50,000), chloroform solutions containing 1.0% (w / v) PVAc2 (the average molecular weight of PVAc2 is 50,000), chloroform solutions containing 1.0% (w / v) PMMA1 (the average molecular weight of PMMA1 is 15,000), chloroform solutions containing 1.0% (w / v) PMMA2 (the average molecular weight of PMM2 is 350,000), chloroform solutions containing 1.0% (w / v) PCL1 (the average molecular weight of PCL1 is 50,000-60,000), and chloroform solutions containing 1.0% (w / v) PCL2 (the average molecular weight of PCL2 is 80,000-100,000), and the outer aqueous phase is an aqueous solution containing 0.5% (w / v) PVA2. The inner oil phase is sheared by the outer water phase in the microchannel to form microdroplets with a particle size of about 145 μm, which are placed in a 5°C constant temperature box for about 48 hours until the organic solvent in the microdroplets evaporates completely to obtain composite microspheres, which are observed under confocal microscope with the same parameters as in Example 1. The fluorescence intensity change results are shown in Fig.28 As shown, the structure and molecular weight of the internal phase solute will affect the aggregation morphology, thereby causing changes in the luminescence intensity. Under 405nm laser excitation, the composite microspheres obtained in this embodiment have higher blue, green and red emission than PMMA-PVA and PCL-PVA composite microspheres; at the same time, the PVAc1-PVA composite microspheres with smaller molecular weight have higher blue, green and red emission than the PVAc2-PVA composite microspheres with larger molecular weight; while the PMMA2-PVA and PCL2-PVA composite microspheres with larger molecular weight only emit more red than the PMMA1-PVA and PCL1-PVA composite microspheres with smaller molecular weight.

[0108] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for regulating the luminescence characteristics of polyvinyl alcohol, characterized in that: An organic solvent is used as an inner oil phase and a polyvinyl alcohol aqueous solution is used as an outer water phase. A droplet microfluidic chip is used to prepare microdroplets in an oil-in-water morphology. The microdroplets are allowed to stand at a constant temperature to volatilize the organic solvent and solidify to form monodisperse microspheres. The effect of regulating the luminescence characteristics of polyvinyl alcohol is achieved by adjusting the microsphere preparation conditions. The microsphere preparation conditions include the selection of an organic solvent in the inner oil phase, components and concentrations added to the organic solvent, components and concentrations added to the polyvinyl alcohol aqueous solution, the constant temperature at which the microdroplets are allowed to stand, the initial particle size of the microdroplets, and the concentration, alcoholysis degree and molecular weight of polyvinyl alcohol in the polyvinyl alcohol aqueous solution.

2. The control method according to claim 1, characterized in that: The organic solvent includes chloroform and dichloromethane.

3. The control method according to claim 1, characterized in that: The components added to the organic solvent include polyvinyl acetate, polymethyl methacrylate and polycaprolactone, the molecular weight of the polyvinyl acetate includes 50,000 and 300,000, the molecular weight of the polymethyl methacrylate includes 15,000 and 350,000, and the molecular weight of the polycaprolactone includes 50,000-60,000 and 80,000-100,000.

4. The control method according to claim 1, characterized in that: The concentrations of the components added to the organic solvent in the organic solvent include 0.2 g / 100 mL, 1 g / 100 mL, 5 g / 100 mL, 10 g / 100 mL and 15 g / 100 mL.

5. The control method according to claim 1, characterized in that: The components added to the polyvinyl alcohol aqueous solution include glycerol, polyethylene glycol and a surfactant, the molecular weight of the polyethylene glycol is 400, and the surfactant includes an anionic surfactant and a nonionic block copolymer surfactant.

6. The control method according to claim 5, characterized in that: The volume concentration of the glycerol includes 10.0% and 30.0%, the volume concentration of the polyethylene glycol is 10.0%, and the concentration of the surfactant is 0.1 g / 100 mL.

7. The control method according to claim 1, characterized in that: The micro-droplet constant temperature static temperature includes 5°C, 20°C, and 30°C.

8. The control method according to claim 1, characterized in that: The initial particle sizes of the micro droplets include 105 μm, 145 μm, and 175 μm.

9. The control method according to claim 1, characterized in that: The concentration of polyvinyl alcohol in the polyvinyl alcohol aqueous solution includes 0.2g / 100mL, 0.5g / 100mL, 1g / 100mL, 2g / 100mL, 3g / 100mL, and 5g / 100mL.

10. The control method according to claim 1, characterized in that: The alcoholysis degree of the polyvinyl alcohol in the polyvinyl alcohol aqueous solution includes 98%, 87-89% and 87-90%, and the molecular weight includes 13000-23000, 30000-70000 and 146000-186000.